Structure-Based Design of Inhibitors of the Crucial Cysteine Biosynthetic Pathway Enzyme O-Acetyl Serine Sulfhydrylase - Mazumder, Mohit; Gourinath, Samudrala (Current Topics in Medicinal Chemistry, 2016)
The cysteine biosynthetic pathway is of fundamental importance for the growth, survival, and pathogenicity of the many pathogens. This pathway is present in many species but is absent in mammals. The ability of pathogens to counteract the oxidative defences of a host is critical for the survival of these pathogens during their long latent phases, especially in anaerobic pathogens such as Entamoeba histolytica, Leishmania donovani, Trichomonas vaginalis, and Salmonella typhimurium. All of these organisms rely on the de novo cysteine biosynthetic pathway to assimilate sulphur and maintain a ready supply of cysteine. The de novo cysteine biosynthetic pathway, on account of its being important for the survival of pathogens and at the same time being absent in mammals, is an important drug target for diseases such as amoebiasis, trichomoniasis & tuberculosis. Cysteine biosynthesis is catalysed by two enzymes: serine acetyl transferase (SAT) followed by O-acetylserine sulfhydrylase (OASS). OASS is well studied, and with the availability of crystal structures of this enzyme in different conformations, it is a suitable template for structure-based inhibitor development. Moreover, OASS is highly conserved, both structurally and sequence-wise, among the above-mentioned organisms. There have been several reports of inhibitor screening and development against this enzyme from different organisms such as Salmonella typhimurium, Mycobacterium tuberculosis and Entamoeba histolytica. All of these inhibitors have been reported to display micromolar to nanomolar binding affinities for the open conformation of the enzyme. In this review, we highlight the structural similarities of this enzyme in different organisms and the attempts for inhibitor development so far. We also propose that the intermediate state of the enzyme may be the ideal target for the design of effective highaffinity inhibitors.
Keywords: O-acetyl serine sulfhydrylase